Valuing interdisciplinary collaborative research beyond impact - Facer, Keri 1972-; Pahl, Kate 1962- (Connected communities (Bristol, England), 2017)
Universities are increasingly taking an active role as research collaborators with citizens, public bodies and community organisations but they, their funders and institutions struggle to articulate the value of this work. This book addresses the key challenges in collaborative research in the arts, humanities and social sciences